Anthropometric effect of a personalized food avoidance dietary approach to stop hypertension - Chioli P Chijioke; Micheal T Okafor; Uzoamaka A Okoli; Imelda N Nubia; Bridget Nwokolo; Ifeoma C Onah; Clinton Ide; Chika Effiong-Essieng; Genevieve Obiefuna; Chikere Anusiem (International Journal of Medicine and Health Development, 2023)
Background: Body anthropometries are indicators of health and disease. It is universally accepted that it is a useful tool for assessing health status. Objective: The aim of this article is to determine the effect of a personalized food avoidance dietary approach to stop hypertension (PFADASH) on anthropometric parameters: body mass index (BMI), triceps skin fold thickness (TSFT), and abdominal circumference (AC) on study participants. Materials and Methods: This was a longitudinal study and part of an open controlled clinical trial of a PFADASH approved by the University of Nigeria Teaching Hospital Ethics Committee. Anthropometric parameters were compared between study participants with good and poor dietary compliance to a PFADASH. Results: There was no significant difference in the anthropometric parameters: BMI, TSFT, and AC among participants with good and poor dietary compliance to a PFADASH (P > 0.05). Conclusion: There was no negative effect of a PFADASH on anthropometric parameters, despite not being a calorie-restrictive dietary intervention.